(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
An investigative study was conducted to determine the left over residue of five commonly used insecticides in cauliflower and yard long bean samples collected from local market of eight different regions like Bogra, Comilla, Dhaka, Gazipur, Jessore, Khagrachari, Rajshahi and Rangpur and carried out to the lab for analysis. Among 47 analyzed vegetable samples, 20 had insecticide residues, of them 11 had above maximum residue limit (MRL) set by FAO/WHO. Of 24 analyzed cauliflower samples, 11 contained residue of cypermethrin, diazinon, quinalphos, fenitrothion and malathion in which 8 had above MRL. Most of the sample contain diazinon and cypermethrin residue. Three samples showed 0.202-0.603 mgkg-1diazinon resides and two samples contain 0.590-0.640 mgkg-1cypermethrin residues which were above MRL. Cauliflower samples also showed two of three multi insecticide residues which were above MRL. Among 23 analyzed yard long bean samples, 9 showed the residue of five tested insecticides but only three had the residue of 0.410 mgkg-1quinalphos, 0.651 mgkg-1malathion and 0.591 mgkg-1cypermethrin which were above MRL and the next 6 samples including three multi insecticide residues were of below MRL. Bogra, Jessore and Comilla showed more residues irrespective of single or multiple insecticide then other locations. No residue of the tested insecticide was found in the samples collected from Dhaka and Rajshahi in both the vegetables. Cauliflower in Khagrachari and yard long bean in Rangpur did not show any insecticide residue. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (3), 547-551